PERBANDINGAN PEMAHAMAN KONSEP MATEMATIS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN MODEL PEMBELAJARAN LANGSUNG SISWA KELAS VII SMPN 22 KABUPATEN TEBO - Niken Siskawati, Ayu Yarmayani (Universitas Batanghari Jambi, 2017)
Abstract :The ability of students' understanding of mathematical concepts is a basic ability to be possessed by students in the learning of mathematics. Cooperative learning comes from the concept that students will more easily find and understand difficult concepts if they discuss each type of cooperative learning model two stay two stray is a learning model that is able to activate students in the group. This research is quasy experiment. population in this study were students of class VII SMPN 22 Tebo which consisted of two classes. Sampling using purposive sampling.Where two classes of samples are given different treatment. From the results of research conducted an average score for the class of experiment was 61.61 with a standard deviation of 12.42 and a control class averages 54.00 with a standard deviation of 12.31. As well as from the results of hypothesis test obtained t of 2.20 and 1.67 t table.The calculation it is seen that t count bigger than ttabel then H1 accepted. Based on the final results can be concluded that the students' understanding of mathematical concepts that apply Cooperative Learning Model Two Stay Two Stray type is better than learning model directly on students in class VII SMPN 22 Tebo. Keyword :Understanding of Mathematical Concepts , Cooperative Learning Model Type Two Stay Two Stray , Direct Learning Model